2023
DOI: 10.1002/jmri.29120
|View full text |Cite
|
Sign up to set email alerts
|

Value of Non‐Contrast‐Enhanced Vessel Wall MR Imaging in Assessing Vascular Invasion of Retroperitoneal Tumors

Ying Cui,
Yufei Zhao,
Xiaohui Chen
et al.

Abstract: BackgroundDue to their location and growth patterns, retroperitoneal tumors often involve the surrounding blood vessels. Clinical decisions on a proper treatment depend on the information on this condition. Evaluation of blood vessels using non‐contrast‐enhanced vessel wall MRI may provide noninvasive assessment of the extent of tumor invasion to assist clinical decision‐making.PurposeTo investigate the performance and potential of non‐contrast‐enhanced vessel wall MRI in evaluating the degree of vessel wall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the ability of vessel wall MRI to detect and monitor atherosclerotic plaques, enhancing the understanding of the disease pathophysiology. 7,8 In this issue of JMRI, Peng et al 9 creatively evaluated the extent of vessel wall invasion in malignant retroperitoneal tumors using non-contrast-enhanced vessel wall imaging, which was validated against surgical confirmation and pathological results. In this study, the degree of vascular wall invasion was classified into five categories, based on the spatial association between the tumor and the vessel wall, as well as the morphology and signal of the vessel wall.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the ability of vessel wall MRI to detect and monitor atherosclerotic plaques, enhancing the understanding of the disease pathophysiology. 7,8 In this issue of JMRI, Peng et al 9 creatively evaluated the extent of vessel wall invasion in malignant retroperitoneal tumors using non-contrast-enhanced vessel wall imaging, which was validated against surgical confirmation and pathological results. In this study, the degree of vascular wall invasion was classified into five categories, based on the spatial association between the tumor and the vessel wall, as well as the morphology and signal of the vessel wall.…”
mentioning
confidence: 99%